Copper Enhances Zinc-Induced Neurotoxicity and the Endoplasmic Reticulum Stress Response in a Neuronal Model of Vascular Dementia - Tanaka, Ken-ichiro; Kawahara, Masahiro (Frontiers in Neuroscience, 2017)
Zinc (Zn), an essential trace element, is secreted by synaptic vesicles during neuronal excitation and plays several critical roles in neuronal information processing. However, excess Zn ion (Zn2+) is neurotoxic and has a causative role in the pathogenesis of vascular dementia. Here, we investigated the molecular mechanism of Zn2+-induced neurotoxicity by using immortalized hypothalamic neurons (GT1-7 cells), which are more vulnerable than other neuronal cells to Zn2+. We examined the effects of other metal ions on the Zn2+-induced neurotoxicity in these cells and found that sub-lethal concentrations of copper ion (Cu2+) markedly exacerbated Zn2+-induced neurotoxicity. The co-administration of Cu2+ and Zn2+ also significantly increased the expression of genes related to the endoplasmic reticulum’s stress response, including CHOP, GADD34, and ATF4. Similar to Zn2+, Cu2+ is stored in presynaptic vesicles and secreted during neuronal excitation. Thus, based on our results, we hypothesize here that Cu2+ interacts with Zn2+ in the synapse to synergistically promote neuronal death and significantly influence the pathogenesis of vascular dementia.